2012
DOI: 10.7598/cst2012.156
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Reliable Gas Chromatography Method for the Determination of 3-Quinuclidinol Content in Solifenacin Succinate Drug Substance

Abstract: A simple and reliable gas chromatography method has been developed and validated for the determination of 3-quinuclidinol content in solifenacin succinate drug substance, using dimethylsulfoxide (DMSO) as internal standard (IS). Efficient chromatographic separation was achieved on DB-Wax, 15 m long with 0.53 mm i.d., 1.0 µm particle diameter column consists with 100% polyethylene glycol as stationary phase including carrier gas as Helium. The analyte and internal standard were extracted in chloroform and monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Its anticholinergicparasympatholytic action 2 reduces the tonus of smooth muscle in the bladder, effectively reducing the number of required voids, urge incontinence episodes, urge severity and improving retention, facilitating increased volume per void. Literature survey revealed that few HPLC [3][4][5][6][7][8][9][10][11] , LC-MS [12][13] , HPTLC [14][15] gas chromatography 16 and spectroscopic [17][18] methods have been reported for the determination of Solifenacin succinate in tablet dosage forms as well as in biological matrices. An attempt has been made to develop a simple and rapid reverse phase liquid chromatographic method for the determination of Solifenacin succinaten in tablet dosage forms which was validated according to ICH guidelines 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Its anticholinergicparasympatholytic action 2 reduces the tonus of smooth muscle in the bladder, effectively reducing the number of required voids, urge incontinence episodes, urge severity and improving retention, facilitating increased volume per void. Literature survey revealed that few HPLC [3][4][5][6][7][8][9][10][11] , LC-MS [12][13] , HPTLC [14][15] gas chromatography 16 and spectroscopic [17][18] methods have been reported for the determination of Solifenacin succinate in tablet dosage forms as well as in biological matrices. An attempt has been made to develop a simple and rapid reverse phase liquid chromatographic method for the determination of Solifenacin succinaten in tablet dosage forms which was validated according to ICH guidelines 19 .…”
Section: Introductionmentioning
confidence: 99%